A clinico-serological investigation of arthritis in patients with or without cryoglobulinemic syndrome - P. Fadda; L. La Civita; A.L. Zignego; C. Ferri (PAGEPress Publications, 2002)
Objective: To compare the clinico-serological features of arthritis from two HCV+ patient groups characterised by mixed cryoglobulinemia (MC) or chronic hepatitis (CH). Methods: We retrospectively studied 157 MC patients (119 females, mean age 64.8 yrs, range 36-88) and 155 CH patients (103 females, mean age 58.8 yrs, range 30-81). Patients with HBV and/or HIV co-infections and a follow-up shorter than 1 year were excluded. MC was classified according to standard criteria, while CH classification was based on Desmet's criteria. Results: No differences in epidemiology were demonstrated between the two series of patients. Although significantly prevalent in MC patients, extra-hepatic manifestations including nephropathy, neuropathy, pneumopathy, mixed cryoglobulins, RF positivity and hypocomplementemia were detected in both patient groups. Arthritis was present in 23 CH (15%) and 12 MC (8%) patients. A symmetrical polyarthritis was observed in 87% of 23 CH patients, while cryoglobulinemic arthritis was invariably asymmetrical and pauciarticular. Unlike MC patients, who had a constantly nonerosive arthritis, in 7/23 CH patients arthritis was erosive. Steroids and/or hydroxycloroquine or D-penicillamine were safe and useful in controlling the arthritis over the short-medium time, although clinical response was more evident in MC patients. Instead, in 5/23 CH and 3/12 MC patients, interferon-alpha treatment was able to trigger or exacerbate the arthritis despite a good control of liver function. Conclusions: HCV infection seems to be, possibly in genetically predisposed patients, responsible for arthritis at times similar to rheumatoid arthritis. In these patients a careful assessment of the interferon-alpha treatment is mandatory owing to the potential 'arthritogenic effect' due to its immunoregulatory properties.